INNOVATION OF ADAPTIF TECHNOLOGY BASED ON INTERNET OF THINGS FOR INCLUSIVE STUDENT - Ahmad Jazuly; Laili Aflahkul Yaum; Khusna Yulinda Udhiyanasari; Renalatama Kismawiyati (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
This paper discusses the learning system of inclusive students by adapting adaptive technology. The learning process is carried out by adjusting the curriculum and educational infrastructure. Students at the PGRI Argopuro Jember University College have 45-50 inclusion students with each batch of 2018-2020. Inclusive students (blind, deaf) experience negative stigma, mentality, difficulty understanding lessons, task completion, and communication. Inastec adaptive technology innovation based on internet of things is proposed to improve the inclusive student learning system. Learning utilizes application algorithms and hardware design schemes for the Respberry Pi 3 B+. The results of applying Inastec's adaptive technology based on the internet of things can help inclusive students in understanding theory, completing assignments, and communicating with the Inastec platform tool with text output and voice feedback on sound speakers.